Pencabutan Peraturan Menteri Perdagangan No 6 Tahun 2022 Perspektif Hukum Islam - Ratna (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
The Ministry of Trade issued a regulation in the form of Minister of Trade Regulation No. 6 of 2022 concerning Setting the Highest Retail Price for Palm Cooking Oil to lower the price of cooking oil on the market. However, this regulation was repealed due to a new problem that arose. This research intends to find out and examine the background to the revocation of this regulation and how Islamic law views the repeal of the Minister of Trade Regulation No. 6 of 2022 concerning Determination of the Highest Retail Price for Palm Cooking Oil. This type of research includes using library research (Library Research), which is a type of research whose data sources are obtained from the literature. This research uses primary data sources and secondary data sources that support the research. The method of data collection is documentation, further action. The method of analysis used in this study is descriptive qualitative analysis with an interactive model (Interactive Model of Analysis), which is then followed by analyzing the data that produces conclusions. This research shows that the repeal of Ministerial Regulation No. 6 of 2022 concerning Determination of the Highest Retail Price for Palm Cooking Oil does not conflict with Islamic law and does not conflict with the views of the majority of scholars who argue that in any situation and condition, whether the price increases caused by traders or caused without the intervention of traders, then any form of interference in price fixing is not justified. The Prophet really appreciated the price formed by the market as a fair price. Rasulullah rejected the existence of price intervention if price changes occur due to a reasonable market mechanism. The market here requires morality, including: fair competition, honesty, transparency and justice. If these values ​​have been established, then there is no reason to reject market prices. ‎ Keywords: Islamic law, pricing, Regulation of the Minister of Trade, Setting the Highest Retail Price, Palm Cooking Oil.